Household Saving and Full Consumption over the Life Cycle - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2001)
This paper extends the standard model of life cycle consumption, saving and labor supply in a number of directions. First, it argues that consumption should be defined as expenditure on household production as well as on market goods, that is, we are interested in life cycle profiles of full consumption. If this is done, several well-known puzzles concerning life cycle consumption behaviour are resolved. Secondly, we stress the importance of the heterogeneity of household behaviour in respect of female labour supply and saving, and provide evidence to show that these are very closely related across households. Finally, we formulate theoretical and empirical models incorporating these ideas and use them to show that policy changes, such as a reduction in the progressivity of income taxation, can have effects that contrast sharply with those suggested in the existing literature.
Keywords: D13; D91; H31; J22; 330; Saving; household production; full consumption; life cycle; Haushaltsproduktion; Gesamtwirtschaftlicher Konsum; Sparen; Lebenszyklus; Theorie